Artistic investigations of itself in a poetic of the solitude (Palíndromo, 2021)
Visual essay that uses iconic elements of a flight routine taking the portrait as a category image This text presents the central points of the development of the Works of the series which compose the artistical project “Re[Di]ssonances”. By expatiate on this proposition, we present thevisions on solitude registered by some exponents of philosophy and literature, which are relatedto the scope of the artistic production in question. By exploring the possibilities of expression ofthe most subjective livingness, we discuss the relation of the artistic practice with the desire onexpress the primordial aspects pertinent to the role of solitude in existence and the paradoxeswhich it contains.
Keywords: Solitude.; Subjectivity.; Artistic creation.; Visual poethic.